Feature Integration Across the Lifespan: Stickier Stimulus–Response Bindings in Children and Older Adults - Hommel, Bernhard; Kray, Jutta; Lindenberger, Ulman (Frontiers in Psychology, 2011)
Humans integrate the features of perceived events and of action plans into episodic event files. Here we investigated whether children (9-10 years), younger adults (20-31 years), and older adults (64-76 years) differ in the flexibility of managing (creating and updating) event files. Relative to young adults, performance in children and older adults was more hampered by partial mismatches between present and previous stimulus-response relations, suggesting less efficient updating of episodic stimulus-response representations in childhood and old age. Results are discussed in relation to changes in cortical neurochemistry during maturation and senescence.